The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.conbuildmat.2020.120700
|View full text |Cite
|
Sign up to set email alerts
|

Does kaolin clay really create a perfect hydraulic interface contact between materials?

Abstract: In literature, kaolin clay is often put forward to create a perfect hydraulic contact across the interface of building materials. This paper studies, based on imbibition experiments, if kaolin clay truly nullifies a hydraulic interface resistance between materials. Thereto, a comparison is made between the water uptake by monolithic samples and by samples composed using kaolin clay. An interface resistance is observed and estimated to be in the order of 6 000 m/s to 12 000 m/s for a high absorptive brick and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Parthasarathy [25] informed that TW is one of the major electronic waste materials posing serious Vereecken et al [27] reported similar kaolin clay composition.…”
Section: Chemical Composition Of the Raw Materials By The Xrf Methodsmentioning
confidence: 99%
“…Parthasarathy [25] informed that TW is one of the major electronic waste materials posing serious Vereecken et al [27] reported similar kaolin clay composition.…”
Section: Chemical Composition Of the Raw Materials By The Xrf Methodsmentioning
confidence: 99%